Effect of calcium hydroxide-based materials on periapical tissue healing and orthodontic root resorption of endodontically treated teeth in dogs - de Souza, Ricardo Sampaio; de Souza, Valdir [UNESP]; Holland, Roberto [UNESP]; Gomes-Filho, Joao Eduardo [UNESP]; Murata, Sueli Satomi [UNESP]; Sonoda, Celso Koogi [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
This study evaluated periapical tissue healing and orthodontic root resorption of endodontically treated teeth sealed with calcium hydroxide in dogs. The sample consisted of three contralateral pairs of maxillary incisors and two contralateral pairs of mandibular incisors in each of two dogs using a split mouth design. After biomechanical preparation of the teeth in the first group (n = 10), a Ca(OH)(2) dressing was placed for 14 days before root canal filling with Ca(OH)(2)-based sealer (Sealapex) and gutta-percha points. In the second group (n = 10), root canals were obturated immediately after the mechanical preparation with gutta-percha points and zinc oxide and eugenol (ZOE)-based sealer (Endofill). After completion of endodontic treatment, the teeth were moved with an orthodontic appliance with a calibrated force of 200 g, reactivated every 21 days. After 105 days, the animals were killed and the teeth were removed upon completion of active treatment, without a period of recovery, and prepared for histomorphological analysis. All sections of each tooth were graded subjectively on a scale from one to four to obtain the average of the 16 histomorphological parameters analysed. Evaluation of the differences between the two treatment protocols was made with Mann-Whitney U-test. It was observed that the teeth treated with Ca(OH)(2)-based materials provided better outcomes (P = 5%), with complete repair of all root resorption areas, high rate of biological closure of the main canal and apical accessory canals by newly formed cementum, less intense and extensive chronic inflammatory infiltrate, and better organization of the periodontal ligament. Under the tested conditions, Ca(OH)(2)-based materials had a favourable action on periapical tissue healing and repair of orthodontic root resorption in endodontically treated dogs' teeth.